Relationship of organizational culture and organizational intelligence in public organization / Nour-Mohammad Yaghoubi, Jamshid Moloudi, Atiyeh Haghi - Moloudi, Jamshid; Haghi, Atiyeh (Faculty of Business and Management & Institute of Business Excellence, 2010)
This research studies the relationship of organizational intelligence (OI) and organizational culture (OC) in Social Security Organization in Iran. Dimensions of OI are Strategic Vision, Shared Fate, and Appetite for Change, Heart, Alignment and Congruence, Knowledge Deployment and Performance Pressure. The type of this research is Descriptive-Correlation. Statistical community was 280 of personnel in 3 levels (managerial, supervisor, employee) that were selected on Stratified Random Sampling. Data were collected by Albrecht OI and Denison organizational culture questionnaire. Data analysis was carried out by using the statistical program packages SPSS. P-value, equal or lower than 0.01, were considered statistically significant. Findings showed that there is statistical significant relation between OI and OC.